Walt Whitman papers - Whitman, Walt, 1819-1892.; Diggins, E. F.; Furness, Clifton Joseph, 1898-1946.; Leech, Abraham; Whitman, Walt, 1819-1892.
Correspondence, literary manuscripts, family papers, printed matter, and miscellany relating to Whitman's life and work. Includes a printed copy of "O Captain! My Captain!" with Whitman's handwritten corrections. Correspondence with Abraham Leech relates to Whitman's life as a schoolteacher in Woodbury and Whitestone, Long Island, N.Y.; his views on small-town life; and his support for the Democratic Party and it's candidate, Martin Van Buren, in the presidential election of 1840. Also includes a diary kept by Leech, 1838-1844; Leech (Leach) family genealogical notes; a plaster bust of Whitman by sculptor E.F. Diggins; and microfilm of Whitman materials in other repositories. Correspondents also include Whitman's mother, Louisa Van Velsor Whitman, and his sister, Hannah Louisa Whitman Heyde.
Reprint of Walt Whitman's "O captain, My captain" with comments by author, 1888 February 9, also available through the Library of Congress Web site.
Microfilm edition of the Clifton Joseph Furness notebook available
Microfilm edition only of originals at various repositories
In part, transcripts and photocopies.
Poet.
Collection material in English.
Keywords: Heyde, Hannah Louisa Whitman, -- 1823-1908 -- Correspondence; Heyde, Hannah Louisa Whitman, -- 1823-1908 -- Correspondence; Lincoln, Abraham, -- 1809-1865 -- Death and burial; Van Buren, Martin, -- 1782-1862.; Whitman, Louisa Van Velsor, -- 1795-1873 -- Correspondence; Whitman, Walt, -- 1819-1892 -- Statues; Leach family -- Genealogy; Whitman family; Democratic Party (U.S.); American literature; American poetry; American prose literature; Busts; City and town life; Education -- New York (State) -- Long Island; Poetry; Presidents -- United States -- Election -- 1840.; Sculpture; Long Island (N.Y.) -- Social life and customs; United States -- Politics and government -- 1815-1861.; Poets